أسعار التنازلات الداخلية كأداة لتحسين أداء مراكز المسؤولية في المؤسسات الاقتصادية - مريم, تواتي (Recherches économiques et managériales; Vol. 12 (2012): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (DÉCEMBRE), 2014)
بوجود التنظيمات غير مركزية يمكن اعتبار مختلف الوحدات ( المراكز ) ككيان حقيقي غير مستقل فيما بينها، و التبادلات التي تتم بين هذه المراكز الخاصة بنفس المنظمة يمكن   أن تتم من خلال سعر، هذا الأخير يسمى " سعر التنازل الداخلي " PCI  "  أو  " سعر الانتقال ( التحويل )، هذا الأخير يسمح بتقييم الأداء المالي للمراكز و هذا بالاعتماد على معيار الربحية، أي  يسمح بمعرفة مراكز المسؤولية التي تحقق مردودية ايجابية منها و التي تحقق مردودية سلبية، و بهذا يمكن لنا التدخل ( في حالة وجود مردودية سلبية )عن طريق عملية التمهين التنظيمي للمعالجة، و هذا من أجل تحسين الأداء و منه زيادة أرباح المراكز بصفة خاصة و المؤسسة بصفة عامة الكلمات المفتاحية : تقييم الأداء ، مراكز المسؤولية ، أسعار التنازلات الداخلية ، التمهين التنظيمي ، تحسين الأداء Abstract: With existence of decentralized organizations, different units (centers) can be considered as a realistic being which is not independent with each other, and exchanges that occur between these centers concerning the same organization can be made through a price, this latter is called "internal price concession" "IPC" or "moving (conversion) price", this latter allows an assessment of the financial performance of centers basing on profitability criterion, so, it allows to identify the responsibility centers that achieve positive and negative effectiveness, accordingly we can intervene (in the case of negative effectiveness) through the process of organized apprenticeship for treatment, and this in order to improve performance and increase centers’ profits in particular, and the institution in general Keywords: Performance evaluation, responsibility centers, internal price rates concessions, organized apprenticeship organizational, performance improvement